2005
DOI: 10.1038/sj.jcbfm.9600144
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Astrocytes and Neurons Studied using a Mathematical Model of Compartmentalized Energy Metabolism

Abstract: Understanding cerebral energy metabolism in neurons and astrocytes is necessary for the interpretation of functional brain imaging data. It has been suggested that astrocytes can provide lactate as an energy fuel to neurons, a process referred to as astrocyte-neuron lactate shuttle (ANLS). Some authors challenged this hypothesis, defending the classical view that glucose is the major energy substrate of neurons, at rest as well as in response to a stimulation. To test the ANLS hypothesis from a theoretical poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
3
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 42 publications
(85 reference statements)
4
147
3
8
Order By: Relevance
“…Recently, we developed models to investigate compartmentalized energy metabolism between astrocytes and neurons (15) and identify mechanisms necessary to explain brain LAC kinetics (16). Using these models, we showed that current experimental data on LAC and NADH kinetics upon various kinds of activation are compatible with the ANLS hypothesis.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, we developed models to investigate compartmentalized energy metabolism between astrocytes and neurons (15) and identify mechanisms necessary to explain brain LAC kinetics (16). Using these models, we showed that current experimental data on LAC and NADH kinetics upon various kinds of activation are compatible with the ANLS hypothesis.…”
Section: Discussionmentioning
confidence: 77%
“…These time evolutions result in conditions favorable to the ANLS. However, as suggested (15,27), ANLS does not require to be a time-invariant phenomenon. More precisely, our results suggest the following sequence of events: (i) an early onset of neuronal oxidative phosphorylation, resulting in the rapid decrease in mitochondrial NADH; and (ii) stimulation of neuronal PDH and Krebs cycle, resulting in a decrease in neuronal PYR and LAC, which induces thermodynamical conditions favorable to a conversion of LAC into PYR and LAC uptake by neurons, which can be reinforced by the favorable kinetic properties of neuronal MCTs (16).…”
Section: Distinct Metabolic Responses Of Neurons and Astrocytes Suppomentioning
confidence: 99%
“…It should be noted that in the presence of cross talk, an external input Na ϩ influx as low as 0.3 mmol·l Ϫ1 ·s Ϫ1 (corresponding to v input ϭ 1) is sufficient to abolish the periodic regime of BOLD oscillations. This is to be compared with the level of Na ϩ influx estimated during focal neuronal activity, which is in the order of 0.5 mmol·l Ϫ1 ·s Ϫ1 after habituation establishes but much higher at stimulus onset (Aubert and Costalat 2005;DiNuzzo et al 2010a), suggesting that a significant neuron-astrocyte cross talk is not compatible with the occurrence of BOLD oscillations during focal brain activity.…”
Section: Resultsmentioning
confidence: 97%
“…The cotransport stoichiometry of GABA recycling is less studied in the literature and, as pointed out in Hertz et al (2007), the Na + stoichiometry accounts for only a fraction of energetic cost in astrocytes. For these reasons, in the present model the activation state is not controlled in terms of Na + flux as, e.g., in Aubert and Costalat (2005) but rather by specifying a target value for the relevant neurotransmitter release, augmented with a nonspecific Figure 4 Top row: average oxygen partitioning among the three cell types in the three different steady states, each computed from a sample of 100,000 configurations. In the two steady states, ES and AS, characterized by assigning a target rate of glutamate efflux, glutamatergic neurons uptake the majority of oxygen, 75% of the total in ES and 67% in AS, with the remaining almost equally split between astrocytes and GABAergic neurons.…”
Section: Discussionmentioning
confidence: 99%